Déficits cognitivos em pacientes com Lúpus Eritematoso Sistêmico (LES) e Lúpus Eritematoso Sistêmico Neuropsiquiátrico (LESNP): uma análise comparativa - Hunayara Lorena Sousa Tavares (2014)
Systemic Lupus Erythematosus is a chronic inflammatory disease of autoimmune origin, whose symptoms can appear in various organs. The symptoms may vary in periods of exacerbation and inactivity, this thesis aimed to investigate cognitive deficits in patients with Systemic Lupus Erythematosus (SLE) and Neuropsychiatric Lupus Erythematosus (NPSLE) compared with healthy controls. First, a systematic literature review of studies was conducted assessing cognitive deficits in patients with SLE and NPSLE. The databases VHL Medline, PubMed Central, Web of Science and the American Psychological Association were used for articles search. Seven articles were selected and the results indicated the presence of cognitive deficits in psychological assessment of SLE, NPSLE patients compared with healthy controls or other chronic diseases. Based on the hypotheses raised in the literature review, a comparative study was conducted with 48 participants, which 19 SLE patients, six NPSLE patients and 23 healthy people. The groups were matched based on sex, age and education. The instruments used were: Wisconsin Card Sorting Test, the Wechsler Adult Intelligence Scale III, Color Trails Test (Forms 1 and 2). The results did not show significant difference between SLE and NPSLE groups. In the other hand, indicate that SLE and NPSLE patients showed lower performance than the non-clinical group for tasks requiring divided attention, short term memory, working memory, abstract reasoning, language, executive functions and visuospatial ability. The results add to the growing evidence for cognitive impairment in SLE and NPSLE patients without complaints or inactive disease.